Pressões antrópicas em múltiplas escalas espaciais na estruturação de comunidades bentônicas - Kele Rocha Firmiano (2018)
Headwater streams in adequate ecological conditions harbor high biodiversity and provide multiple ecological services to human well-being (e.g., water for human uses including water supply and agriculture irrigation). However, the intensification of human activities has altered the integrity of these ecosystems at different spatial scales, leading to biodiversity loss at global scale. The main goal of this PhD thesis was to evaluate the effects of anthropogenic pressures on multiple spatial scales on benthic macroinvertebrates community structure, at headwater streams in the Neotropical savanna. The thesis was divided into two chapters. The first chapter shows the importance of anthropogenic stressors based on Ephemeroptera assemblage thresholds. Anthropogenic stressors observed at the local and catchment scales without significant correlation with natural environmental variability were selected. Most of Ephemeroptera genera responded negatively to the threshold values detected as percentage of urban areas increased (catchment scale); riparian zone changes, siltation, and water quality decreased (local scale). The chapter two shoes the importance of habitat selection and dispersal limitation to benthic macroinvertebrate metacommunities structure. The benthic macroinvertebrates were classified according to their pollution tolerances and dispersal ability in aquatic and terrestrial environments. The environmental distance (local scale) and four physical distances (regional scale) were calculated to evaluate the importance of habitat selection and dispersal limitation for the metacommunity structure. The environmental distance was calculated based on physical habitat metrics and water quality parameters. Physical distances were calculated based on the drainage network and landscape resistance to dispersal ability, as (i) null distance (surrogate of Euclidean distance), (ii) topographical distance and (iii) land use distance. The most important ecological processes for metacommunity structure were habitat selection and dispersal limitation due to landscape resistance. The environmental distance explained the increase in dissimilarity of all macroinvertebrates considered as weak and moderate dispersers, regardless of their pollution tolerances. The drainage network distance explained the increase in dissimilarity of macroinvertebrates classified as moderate and sensitive to pollution and, for those classified as strong dispersers and tolerant to pollution. The dissimilarity of all groups, except for those considered moderate and resistant to pollution increased as a function of landscape resistance due to land use intensification. The results of this thesis reveal the importance of anthropogenic pressures on headwaters streams at multiple spatial scales (from streams to hydrological units) using benthic organisms as bioindicators of water quality and ecological degradation by human activities.